INTERNALISASI ETOS FASTABIQUL KHAIRAT DALAM PENGELOLAAN KEUANGAN MADRASAH - Aripratiwi, Ratna Anggraini (Universitas Muhammadiyah Tangerang, 2024)
This research aims to construct the fastabiqul khairat ethos in the madrasah financial accountability process. Madrasas are one of the public sector organizations that provide educational services. The research method used is a qualitative method through the construction paradigm. So far, the accountability system applied is western in theory and tends to be pragmatic in nature. That accountability is only to interested parties. By constructing values in the fastabiqul khairat ethos, we are able to deliver a concept of sincerity accountability that has more religious value and prioritizes an attitude of trust. So that it can provide implications in terms of the resulting financial reports being more trustworthy and useful.